Influence of endogenous glucagon-like peptide-2 on lipid disorders in mice fed a high-fat diet. (1st October 2016) - Baldassano, Sara; Amato, Antonella; Rappa, Francesca; Cappello, Francesco; Mulè, Flavia
ABSTRACT: Aim : The purpose of the present study was to investigate the influence of endogenous glucagon-like peptide-2 (GLP-2) on lipid profile in mice fed a standard diet (STD) or a high-fat diet (HFD).Materials and methods : HFD- and age-matched STD mice were injected once a day with GLP-2 (3–33), a GLP-2 receptor (GLP-2R) antagonist, or vehicle for 4 weeks.Results : HFD mice displayed increased intrahepatic lipid concentration and hepatic steatosis and higher plasma concentrations of cholesterol, LDL, AST, and ALT than STD mice. No difference was observed in lipid fecal elimination. In STD mice, the chronic treatment with GLP-2 (3–33) did not affect any parameter, while in HFD mice, it enhanced plasma triglycerides, cholesterol, ALT, and AST and reduced HDL, it increased intrahepatic lipid concentration, and it worsened the hepatic steatosis degree, without affecting lipid fecal elimination.Conclusions : The present results suggest that GLP-2R antagonism worsens lipid disorders in HFD mice, and endogenous GLP-2 might even exert a defensive role against lipid imbalance.